2014
DOI: 10.1093/ntr/ntu186
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of an Examination of Electronic Cigarette User Puff Topography: The Effect of a Mouthpiece-Based Topography Measurement Device on Plasma Nicotine and Subjective Effects

Abstract: In experienced ECIG users, measuring ECIG topography did not influence ECIG-associated nicotine delivery or most measures of withdrawal suppression. Topography measurement systems will need to account for the low flow rates observed for ECIG users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(171 citation statements)
references
References 22 publications
11
160
0
Order By: Relevance
“…The fact that puff velocity does not influence nicotine yield may explain why ECIG user puff topography is associated with velocities that are less than those of cigarette smokers. 30 That is, although a high-velocity puff increases combustion rate and therefore increases the rate at which nicotine is converted from the leaf to the smoke in a tobacco cigarette, it does not increase the rate at which nicotine is emitted from an ECIG. Experienced ECIG users may have learned with practice that the greater effort associated with higher velocity does not influence nicotine-mediated subjective effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that puff velocity does not influence nicotine yield may explain why ECIG user puff topography is associated with velocities that are less than those of cigarette smokers. 30 That is, although a high-velocity puff increases combustion rate and therefore increases the rate at which nicotine is converted from the leaf to the smoke in a tobacco cigarette, it does not increase the rate at which nicotine is emitted from an ECIG. Experienced ECIG users may have learned with practice that the greater effort associated with higher velocity does not influence nicotine-mediated subjective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Puff durations were chosen to approximate that of a typical cigarette smoker (2 s), 6,27 an experienced ECIG user taking an average length puff (4 s), 6,27 and an experienced ECIG user taking a puff of the more extreme length observed (8 s). 27 Puff velocity was chosen to approximate that observed in tobacco cigarette smokers (33 ml/s), 18,28,29 but because experienced ECIG users may puff more slowly, 30 we also examined the effects of a lower velocity (17 ml/s). As Table 1 shows, puff duration and velocity were combined to yield five distinct puff profiles representing a tobacco cigarette smoker (2 s, 33 ml/s), an average ECIG user using low flow (4 s, 17 ml/s), an average ECIG user using a high flow (4 s, 17 ml/s), an extreme ECIG user using low flow (8 s, 17 ml/s), and an extreme ECIG user using a high flow (8 s, 33 ml/s).…”
Section: Aerosol Generation and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying E-Cig exposure is very much like trying to hit a moving target, but one where researchers are not completely sure what the target looks like, since E-Cig devices, the way that they are used, and the types/flavors of e-liquids available are constantly changing. However, some facts have been established: 1) current E-Cig devices deliver nicotine at comparable levels to cigarettes, and certainly at levels high enough to evoke physiological responses in humans and rodents (54,103,138), 2) nicotine is highly addictive and, along with its metabolites, can cause cancer and affect neuronal development in adolescents irrespective of its source (50,155), 3) e-liquids have been shown to contain potentially toxic aldehydes and ROS (146), and 4) some type of a biological response (e.g., change in cytokine levels) has been observed in the vast majority of murine in vivo and in vitro studies following E-Cig vapor/e-liquid exposure (94,133,152). Although it seems certain that E-Cig aerosols contain toxicants, it is fair to say that they likely contain less types of toxicants than cigarette smoke (i.e., E-Cig aerosols likely have hundreds of chemicals in them while tobacco smoke has thousands of chemicals).…”
Section: Effects Of E-cig Aerosols and E-liquids On Cultured Cells Frmentioning
confidence: 99%
“…10 Among experienced users using their preferred product it was found that 10 puffs at 16 ng/ml could give an increase in plasma nicotine concentrations similar to tobacco cigarettes. 11 Some pulmonary absorption of nicotine seems to take place since peak nicotine levels were achieved within 5 min of starting ENDS use. The study also found that the amount of nicotine obtained by users increases over time as users become more experienced.…”
mentioning
confidence: 99%